-6(u-8)=8u-8

Simple and best practice solution for -6(u-8)=8u-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(u-8)=8u-8 equation:



-6(u-8)=8u-8
We move all terms to the left:
-6(u-8)-(8u-8)=0
We multiply parentheses
-6u-(8u-8)+48=0
We get rid of parentheses
-6u-8u+8+48=0
We add all the numbers together, and all the variables
-14u+56=0
We move all terms containing u to the left, all other terms to the right
-14u=-56
u=-56/-14
u=+4

See similar equations:

| 7x-32=9x-60 | | √(〖3x〗^7-〖2x〗^3)/4x=〖(3x)〗^2+2 | | -4u-44=-6(u+7) | | u9=512 | | 1/3x+2/5x=77 | | -4u-44=-6(u=7) | | p-8=2p-58=p+15 | | √(3x7+2x3)/4x=(3x)2+2 | | M-7=7x9 | | -4(v-3)=-9v+22 | | 4(2x+5)=-28 | | 42=-6/5u | | 6x^+17x-14=0 | | -18=2y+2(y+5) | | 4x-500x^-2=0 | | 56x^+113x+56=0 | | x+.0317x=83798 | | 4m−2m+4=−1+13 | | 7χ²-13(7x)-7=0 | | 20=6(x+2)-2x | | 3x+20=x+25=x+20 | | 6=3v-3 | | 12x=20=15x-38 | | x=(6*x)+7=77 | | 4n-18+n+9=151-5n | | 9=10x10x= | | x(6*x)+7=77 | | 3x+55=8×+15 | | 2d+7=5d | | 2x-3=(x+4) | | 3x2-x+4=0 | | 50+(2x-50)=180 |

Equations solver categories